Chinese cultural theme parks: text mining and sentiment analysis. Issue 1 (4th March 2022) - Zhang, Tingting; Li, Bin; Hua, Nan
ABSTRACT: This paper aims to explore cultural aspects and factors of Chinese theme parks and identify the sentiment of tourists' online reviews, thus bridging the academic gap of a lack of knowledge on the theme park industry's cultural aspects. This research adopted social media analytics and explored 18, 753 original reviews in 160 Chinese cultural theme parks. The results identified nine cultural aspects, and tourists' attitudes among them are sorted in descending order as follows: historical figures and Chinese history/dynasties, folk art and traditional crafts, myths and legends, traditional architecture, literature and painting, drama and dance, folk customs and beliefs, traditional flowers and plants, and traditional food. Moreover, this paper identified the effects of cultural aspects of theme parks on tourists' sentiment, which provided further insight for industry practitioners in setting marketing and operation strategies.